Production of ultrapure hydrogen in a Pd-Ag membrane reactor using Ru/La2O3 catalysts - Faroldi, Betina María Cecilia (2007)
Ru catalysts supported on lanthanum oxide with different loadings were prepared by wet impregnation. These solids were characterized by laser Raman spectroscopy (LSR), XPS, XRD and TPR. The catalytic activity toward hydrogen production through the dry reforming of methane was determined in a fixed-bed reactor and a membrane reactor. The reaction rate expressed per gram of Ru decreased when the metal loading increased. In the Pd-Ag membrane reactor, when the sweep gas flow rate (SG) increased, the conversions overcame the equilibrium values and the difference between CH4 and CO2 conversions decreased. Both Ru(0.6) and Ru(1.2) catalysts were able to restore the equilibrium for the dry reforming reaction up to values of SG = 30 ml min-1; Ru(0.6) was the most effective catalyst. By employing a CO2/CH4 = 1 and a SG of 0.05 mmol s-1, both a high H2 permeation flux of 5.68 × 10-7 mol s-1 m-2 and a hydrogen recovery of 80% were obtained. Both the TPR and the Raman spectroscopy data indicated the presence of Ru(III) strongly interacting with La. Significantly, this observation was further confirmed by the appearance of Ru(III) on the surface. When the Ru content increased, the higher Ru 3d binding energy component was proposed as arising from Ru(IV). Concerning the Ru(1.2) solid, the presence of Ru(IV) was detected by means of TPR experiments, in agreement with the high proportion of Ru(IV) on the surface. Therefore, a fraction of Ru loading was present in this solid as species with weaker metal-support interaction leading to the slight deactivation of this catalyst in the membrane reactor.